If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(6T + -6T + -6T) = -120 Combine like terms: 6T + -6T = 0 -2(0 + -6T) = -120 -2(-6T) = -120 Remove parenthesis around (-6T) -2 * -6T = -120 Multiply -2 * -6 12T = -120 Solving 12T = -120 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Divide each side by '12'. T = -10 Simplifying T = -10
| 8(3x-2)+6=7(-6x-20)-2 | | 3p-2-7p=-5+p-4-4p | | 28(-5+y)+11y=16 | | -16y-1+16y=-12 | | 8(3x-2)+6=7(-6x-20)-1 | | x(1+4)=x | | 8y+7=23 | | 8(3x-2)+6=7(-5x-20)-1 | | x^2+12x=-43 | | 3p-2-7p=-5+p-4p | | 3x^2*8x^5= | | n-3=-4n-(n-3) | | 2y-3y+-1=4 | | -7(3r-4)=-20+9r | | 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 |